1994
DOI: 10.1002/jmv.1890440311
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of hepatitis C virus isolates by a modified polymerase chain reaction assay using type specific primers: Epidemiological applications

Abstract: A polymerase chain reaction (PCR)-based assay using primers against the hepatitis C core gene has been described [Okamoto et al. (1992a): Journal of General Virology 73:673-679]. Within the two major HCV genotypes 1 and 2, the Okamoto system identifies two subtypes each (1a, 1b and 2a, 2b, respectively). Typing is achieved by a primary PCR with consensus primers followed by a nested PCR with type specific primers. The original assay was modified by addition of a parallel second PCR identifying the recently des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 31 publications
1
67
0
Order By: Relevance
“…4, 1999 prevalence of the patients with HCV-2b infection among chronic hepatitis C in Japan is only 5%, 6,37 whereas HCV-2b or -2c is more prevalent than HCV-2a in other geographic areas. [45][46][47][48] Therefore, detailed information related to the HCV subtypes of the study population is necessary for interpreting the HCV study from the different geographic areas where the distribution of HCV subtypes is dissimilar. 44,49,50 Thus, the virological or clinical differences between HCV-2a and -2b infection should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…4, 1999 prevalence of the patients with HCV-2b infection among chronic hepatitis C in Japan is only 5%, 6,37 whereas HCV-2b or -2c is more prevalent than HCV-2a in other geographic areas. [45][46][47][48] Therefore, detailed information related to the HCV subtypes of the study population is necessary for interpreting the HCV study from the different geographic areas where the distribution of HCV subtypes is dissimilar. 44,49,50 Thus, the virological or clinical differences between HCV-2a and -2b infection should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…z 'g'~'n was probably transmitted to Europe through in-.s Z z; _ _ o > travenous drug use. Genotype la is predominant in the US, Canada and Northern Europe [5,6,26]. It has Z \ been associated with transmission by stored blood products [27] and intravenous drug use [7,23].…”
Section: Discussionmentioning
confidence: 99%
“…The major groupings of sequence variants are designated HCV types and the more closely related groups observed within some types are termed subtypes following the classification system proposed by Simmonds and other researchers [4]. The genotyping of HCV isolates has become important for epidemiological purposes [5][6][7]. Several studies have suggested the existence of biological differences between HCV genotypes which affect their capacity for producing liver disease and sensitivity to interferon treatment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, a phylogenetic analysis of the 5Ј-UTR sequences was able to identify genotype 1 but it did not distinguish subtype 1a from subtype 1b. In addition, analysis of all genotype 1 isolates for the putative subtype-specific mutation at position Ϫ99 (A/G) expected to distinguish 1a from 1b (18,42) was in fact unable to distinguish 1a from 1b. Within genotype 1, nucleotide A at position Ϫ99 was always subtype 1a whereas nucleotide G on the same position was either subtype 1b (33%) or 1a (66%).…”
Section: Vol 41 2003 Hcv Subtyping Of Danish Isolates 1095mentioning
confidence: 98%
“…Many different typing methods have been used, all of which depend on a few relatively specific nucleotide changes: RT-PCR using type-specific amplification (18,42), hybridization of RT-PCR products with type-specific probes (34), restriction fragment length polymorphism of RT-PCR amplicons (27), or heteroduplex mobility analysis of RT-PCR amplicons (41). However, these methods were often found not to be definitive, as more sequence data became available.…”
mentioning
confidence: 99%